Effects of one week different intensity endurance exercise on cardiorespiratory and cardiometabolic markers in junior young athletes - Soumitra Mondal; Gashaw Tesema; Mala George; D Mathivana (BMJ Open Sport & Exercise Medicine)
Background Endurance training in varied intensity zones are more likely to show different adaptive responses. However, it is still unclear the intensity level of endurance exercise in junior young athletes that may promote increased markers for cardiorespiratory and cardiometabolic response. Therefore, we aimed to investigate the effect of 1 week different intensity endurance training on markers of cardiorespiratory and cardiometabolic response in young athletes.Methods Thirty apparently healthy male young athletes averaging 19.4±1.3 years of age were recruited and randomly assigned to two different intensity endurance training groups. The first group trained at 60% to 70% maximum heart rate (HRmax) for 45 min per session and the second group trained at 70% to 80% HRmax for 30 min per session for a period of 1 week three sessions per week. A pre-training and post-training, marker of cardiorespiratory and cardiometabolic response was assessed for both groups.Results Both intensity training had no significant effect on markers of cardiorespiratory response within and between training groups (p>0.05). Whereas, cardiometabolic markers lactate dehydrogenase (p=0.001), cardiac troponin I (p=0.001) and creatinekinase myocardial band (p=0.001) significantly increased at the end of 1 week within the group in both training groups (p≤0. 05). In the comparative analysis between groups, there was no significant difference in markers of cardiometabolic response (p>0.05).Conclusion 1 week 60% to 70% HRmax and 70% to 80% HRmax intensity zones induces similar acute effects on markers for cardiometabolic and cardiorespiratory responses between groups and significant elevations of cardiometabolic markers within the groups in moderately trained young athletes.